Multicultural education during pandemics - Sucipto, Sucipto (Technium Social Sciences Journal, 2022)
As a result of cultural, ethnic, racial, and religious variety, multicultural education aims to help students reach their full potential. The philosophy of cultural diversity based on equality, mutual respect, acceptance, and understanding, as well as a moral commitment to social justice, is at the heart of multicultural education. After World War II, a slew of new ideas and concepts concerning multiculturalism began to emerge in education. To comprehend interculturalism, one must consider advances in international politics, including human rights and independence from colonialism, as well as the rising diversity among western nations due to increased migration from newly independent countries. And Europe, too, of course. An attitude of "caring" and "wanting to understand (different") or "politics of recognition," the politics of recognizing persons from minority groups, is the foundation of multicultural education. A broader view of society is taken in multicultural education. On the basis of the fundamental belief that the attitude of "indifference" and "non-recognition" is not just founded in the inequity. In light of the COVID-19 outbreak, I’ve decided to write on intercultural education.